2015
DOI: 10.1093/jxb/erv351
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide annotation and characterization of CLAVATA/ESR (CLE) peptide hormones of soybean (Glycine max) and common bean (Phaseolus vulgaris), and their orthologues ofArabidopsis thaliana

Abstract: HighlightUsing a genome-wide approach, the complete CLE peptide-encoding gene families of soybean and common bean were identified, characterized, and compared with those of Arabidopsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 85 publications
(164 reference statements)
7
81
0
Order By: Relevance
“…Our ITC data of the TDIF mutants suggests, TDIF-H1 contributes most to the binding of the N-terminal anchoring site, while TDIF-E2 plays a marginal role in this interaction. H1 is conserved in TDIF, CLE42, and CLE46 (S1 Fig), which have been classified into the same group [11, 37, 38]. Changing E2 to G in CLE42 does not influence the binding significantly, while E2K, V3H, I10T and S11G substitutions in CLE46 render it unable to bind TDR (Fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…Our ITC data of the TDIF mutants suggests, TDIF-H1 contributes most to the binding of the N-terminal anchoring site, while TDIF-E2 plays a marginal role in this interaction. H1 is conserved in TDIF, CLE42, and CLE46 (S1 Fig), which have been classified into the same group [11, 37, 38]. Changing E2 to G in CLE42 does not influence the binding significantly, while E2K, V3H, I10T and S11G substitutions in CLE46 render it unable to bind TDR (Fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…japonicus , Phaseolus vulgaris , and A . thaliana (Alves‐Carvalho et al, ;Cock & McCormick, ; Hastwell et al, , ). The search yielded 40 unique CLE peptide‐encoding gene candidates of pea (Figure , Table S1) and a further eight sequences with unclear gene structures and/or analogous CLE peptide domains (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…CLE peptide‐encoding genes in P . sativum were identified using BLAST searches of known legume genes identified in Hastwell, de Bang, Gresshoff, and Ferguson () and Hastwell, Gresshoff, and Ferguson () as well as those from Arabidopsis thaliana (Cock & McCormick, ) with E value = 1 (Altschul et al, ; Altschul et al, ). The searches were conducted in The Pea RNA‐Seq gene atlas (http://bios.dijon.inra.fr/FATAL/cgi/pscam.cgi; Alves‐Carvalho et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8,9 The CLE genes have been found in many plant species, whereas the roles of most identified CLE genes remained to be elucidated. 2,[10][11][12][13][14][15] As the 2 most known members of CLE peptide family, AtCLV3 and AtCLE40 are key regulators in coordinating stem cell homeostasis in the SAM (Shoot Apical Meristem) and RAM (Root Apical Meristem), respectively. 1 Other than their functions in stem cell fate, it has been also revealed that the CLE peptides are important players in modulating various plant growth and developmental processes such as nodulation, [16][17][18] protoxylem formation, 19 embryogenesis and endosperm development, 20 phloem formation, 21 pollen growth, 22 and lateral root expansion.…”
Section: Introductionmentioning
confidence: 99%